2014
DOI: 10.1007/s40489-014-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Children with Autism in the Inclusive Preschool Classroom: A Systematic Review of Single-Subject Design Interventions on Social Communication Skills

Abstract: Changes in legislation have led to an increased push for children with autism spectrum disorder to be educated in classrooms with typically developing peers. This systematic review of the literature between the years of 2005 and 2012 aimed to identify effective interventions to support the children with autism spectrum disorder in the inclusive preschool classroom. Single-subject studies concerning the improvement of social communication skills for children with autism spectrum disorder in inclusive preschools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 73 publications
0
32
0
2
Order By: Relevance
“…Social skills have a greater impact on the quality of life for individuals with high functioning autism than do any specific diagnoses and/or cognitive advantage (Mordre et al, 2012). Therefore, implementing appropriate evidence-based strategies for social intervention early and continuing those interventions throughout one's educational tenure, is the most optimal approach to meeting the social needs of students with autism (Hansen et al, 2014;Starr, Popovic, & McCall, 2016).…”
Section: Deficits In Social Skills Impact Many Life Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social skills have a greater impact on the quality of life for individuals with high functioning autism than do any specific diagnoses and/or cognitive advantage (Mordre et al, 2012). Therefore, implementing appropriate evidence-based strategies for social intervention early and continuing those interventions throughout one's educational tenure, is the most optimal approach to meeting the social needs of students with autism (Hansen et al, 2014;Starr, Popovic, & McCall, 2016).…”
Section: Deficits In Social Skills Impact Many Life Domainsmentioning
confidence: 99%
“…(Sansosti & Sansosti, 2012, p. 917). Hansen et al, (2014) conducted a literature review of multiple single-case design research studies; the researchers noted that more than any other support, children with autism in inclusive settings need access to evidence-based practices for social skills to be successful.…”
Section: Introductionmentioning
confidence: 99%
“…Hansen, Blakely, Dolata, Raulston, and Machalicek (2014) found children with ASD can benefit from increased opportunities to observe, initiate social interactions, and respond to the social and play bids of typically developing peers inclusive educational settings offer. Previous studies have shown children with ASD in inclusive classrooms have increased the development of social interaction in both communication skills and group activities (Runcharoen, 2014), and their untargeted verbal initiations greatly improved over baseline levels and often approximated the levels of their peers (Rotheram-Fuller et al, 2010).…”
Section: Benefit Of Inclusive Education For Children With Autism Specmentioning
confidence: 99%
“…Inclusive education is considered the highest goal to facilitate access, success, and participation for children with ASD and the most preeminent educational setting for the development of the majority of children with ASD. Changes in legislation have led to an increased push for children with ASD to be educated in classrooms with typically developing peers (Hansen et al, 2014). The number of students with ASD detected in mainstream schools is increasing (Humphrey, 2008).…”
Section: Research Of Inclusive Education In the Worldmentioning
confidence: 99%
“…Individuals with Autism Spectrum Disorders (ASD) exhibit delay in the development of language and speech (Achmadi et al, 2014). A child with these symptoms will exhibit difficulties in learning and participating in an educational atmosphere unless the conditions are addressed early (Hansen et al, 2014). Numerous techniques and treatments are utilized today to assist children with ASD in learning.…”
Section: Introductionmentioning
confidence: 99%